(untitled) (Trabalho & Educação, 2018)
The studies presented in this article are rooted in the Marxist tradition of critique of political economy and have the Marxist Theory of Dependence (TMD) as a theoretical basis for the analysis of the particularities of dependent capitalism. We aim to discuss the current relationship between labor mobility and overexploitation of the labor force. We approached the temporary migration of workers from the Jequitinhonha Valley to work in the sugar and alcohol sector, demonstrating the intrinsic relation between their status as migrants and the deepening of the overexploitation of their workforce, presenting perverse facets, going beyond the extension and intensification of the Work and also through the increasingly direct domination of their lives. In view of the dynamics of Brazilian dependent capitalism, we present the historical movement of land and labor relations in the region and its relation with the so-called modernization processes of the country, which culminates in the permanent expulsion of these workers from the region; We also present the agribusiness dynamics in the sugar and alcohol industry to expose the mechanisms of accentuation of the extraction of surplus value, which culminate in a greater overexploitation, degradation and accentuation of the objective and subjective misery of migrant workers. ___ Os estudos apresentados neste artigo se arraigam na tradição marxista da crítica à economia política e tem a Teoria Marxista da Dependência (TMD) como base teórica para a análise das particularidades do capitalismo dependente. Temos por objetivo discutir a atualidade da relação entre a mobilidade do trabalho e a superexploração da força de trabalho. Abordamos a migração temporária de trabalhadores do Vale do Jequitinhonha para o trabalho no setor sucroalcooleiro, demonstrando a intrínseca relação ente sua condição de migrantes e o aprofundamento da superexploração de sua força de trabalho. Para estes trabalhadores, a superexploração apresenta facetas perversas, indo além da extensão e intensificação das jornadas de trabalho à dominação cada vez mais direta de suas vidas. Para tanto, tendo em vista a dinâmica do capitalismo dependente brasileiro, apresentamos o movimento histórico da relação terra e trabalho na região e sua relação com os chamados processos de modernização do país, que culmina na permanente expulsão desses trabalhadores da região; apresentamos também a dinâmica do agronegócio no setor sucroalcooleiro para expor os mecanismos de acentuação da extração da mais-valia, que culminam numa maior superexploração, degradação e na acentuação da miséria objetiva e subjetiva dos trabalhadores migrantes.